Laser technologies in treatment of cervical intraepithelial neoplasia (review) - D. A. Tzerkovsky; V. V. Dunaevskaya (Biomedical Photonics)
This review article discusses the key aspects of the use of laser technologies, namely, laser vaporization (LV) and photodynamic therapy (PDT), in the treatment of patients with cervical intraepithelial neoplasia (CIN). The authors analyzed and systematized the foreign experience of these methods of treatment, their indications and contraindications, as well as the advantages over traditional approaches to the treatment of this pathology. The main advantages of the LV are the possibility of complete evaporation of the pathological focus, visual control over the depth of tissue destruction, the absence of prolonged edema and cicatricial deformities, which allows maintaining the integrity of the cervix and its reproductive function. Despite the low trauma and low frequency of adverse reactions, the data on the effectiveness of LV are quite contradictory and, according to various authors, vary from 50% to 98%. To date, there is a significant amount of accumulated experience in the use of PDT with various photosensitizing agents (5-aminolevulinic acid (5-ALA), hematoporphyrin and chlorin and their derivatives) in the treatment of patients with CIN. The main advantages of the PDT are minimal toxicity to the surrounding normal tissues due to the selective accumulation of photosensitizer in pathological tissues, a low risk of severe pain syndrome, the absence of mechanisms of primary and acquired resistance, the possibility of an outpatient treatment session, the possibility of combining with other methods of therapeutic action, the absence of limiting cumulative doses of photosensitizers and light exposure, the possibility of multiple repetitions of the session, good cosmetic results and the possibility of implementing an organ-preserving method of treatment. The obtained results indicate good tolerability of the method (no severe adverse reactions) and a fairly high efficiency of PDT: the frequency of complete regressions varies from 30% to 67% - for application forms of 5-ALA and from 90% to 98.1% - for hematoporifirin and chlorin photosensitizers. Thus, LV and PDT can be considered safe and effective treatment options for patients with CIN.